We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
340
1
avatar

-3-2(2x-1)=-3(2x-5)-10

 Dec 11, 2017
 #1
avatar+104712 
+2

-3-2(2x-1)=-3(2x-5)-10     simplify

 

-3 - 4x + 2  = -6x + 15 - 10

 

-4x -  1  =  -6x + 5        add 1, 6x to both sides

 

2x  =  6           divide both sides by 2

 

x  =  6 / 2  =   

 

 

 

cool cool cool

 Dec 11, 2017

21 Online Users

avatar